Do cash transfers deter migration? - Michael A. Clemens (Institute of Labor Economics (IZA), 2022)
Conditional Cash Transfers are increasingly used by development aid agencies to reduce the incentives for migration from low-income countries. The evidence to date suggests that such transfers typically increase the rate of migration when they are conditional on investment, such as investment in education. They do this primarily by facilitating acquisition of human capital and by lowering capital constraints-increasing both migration aspirations and the means to achieve them. But with certain design features, particular transfer programs have reduced the incentive to migrate. Broadly speaking, migration can be deterred by transfer programs that are conditional on presence in the origin country-provided that the condition is strict, targeted, and lengthy.
Keywords: F22; F35; O15; 330; migration; emigration; irregular; refugee; cash; transfer; income; assistance; aid; insurance; CCT; education; selection; policy; asylum; migrant; immigrant